ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU DENGAN KONSEP ECONOMIC ORDER QUANTITY (EOQ) PADA CV BREGAS LIKUPANG TIMUR MINAHASA UTARA - Rostianti Blongkod; Ventje Ilat; Lidia Mawikere (GOING CONCERN : JURNAL RISET AKUNTANSI, 2023)
Control and determination of the amount of raw material inventory is important for companies so that they can produce efficiently and make sales smoothly. The purpose of this study was to determine the analysis of raw material inventory control using the Economic Order Quantity method. The method used in this research is descriptive research with a qualitative approach. Data on the quantity of raw material orders, costs incurred in the production process, and also the production process carried out by the company. The results of this study indicate that the inventory of raw materials with the EOQ method is more efficient than company policy, the total cost of inventory issued by the company is higher and the frequency of ordering is also more than the Economic Order Quantity method, the cost of inventory issued is lower and the frequency of ordering is also higher. a little.